THE INFLUENCE OF CAPITAL ADEQUACY RATIO, NON-PERFORMING LOANS, AND OPERATIONAL EXPENSES TO OPERATIONAL INCOME ON THE FINANCIAL PERFORMANCE OF PT BANK NEO COMMERCE TBK - Euis Nessia Fitri (Jurnal Ekonomi, 2023)
This study aims to examine the influence of Capital Adequacy Ratio (CAR), Non-Performing Loans (NPL), and Operational Expenses to Operational Income (BOPO) on the financial performance of PT Bank Neo Commerce Tbk, measured by Return on Assets (ROA). A quantitative approach with a causal research design was applied. The study used secondary data derived from the published financial statements of PT Bank Neo Commerce Tbk, the Financial Services Authority (OJK), and Bank Indonesia, covering the period from 2017 to 2022. The population consisted of all financial reports during this period, with the sample selected through purposive sampling. The data were converted into monthly time-series through interpolation to enhance analysis granularity. Classical assumption tests and multiple linear regression analysis were conducted using SPSS. The results indicate that CAR positively and significantly affects ROA, while NPL has a negative and significant effect. BOPO, however, does not significantly influence ROA. The model demonstrates strong explanatory power regarding financial performance.